Retrospective Analysis of Prognostic Value of Optical Coherence Tomography Angiography for the Development of Glaucomatous Damage – One Year Follow-Up Retrospective Observational Cohort Analysis - Bollinger, Olivia; Gugleta, Konstantin; Schmetterer, L.; Hasler, Pascal W.; Min, Jacqueline Chua Yu; Kee, Damon Wong Wing (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Detecting glaucoma damage progression is an essential component of follow-ups in glaucoma patients. It is still unclear which of the currently available and routinely used parameters of glaucoma damage heralds the loss of retinal ganglion cells first. We analysed local hospital data on primary open-angle glaucoma (POAG) patients and looked for correlations between the optical coherence tomography (OCT) structural, OCT angiography (OCTA), and visual field (VF) parameters.Patients and Methods Results of eye examinations of POAG patients at baseline, 6 months, and 12 months were analysed. Inclusion criteria were, apart from the diagnosis of POAG, availability and quality of all modalities of examination data and no surgical intervention on the eyes during the observation period. Data on VF mean defect (MD), OCT peripapillary nerve fibre layer (RNFL), OCT macular ganglion cell layer, and OCTA, peripapillary and in the macula, were parameters of interest. Correlations of structural (OCT and OCTA) on one, and functional parameters (VF MD) on the other side, at baseline and as changing over time (first 6 months vs. second 6 months) were performed.Results All together, data from 78 eyes of 78 POAG patients were included in the analysis. Correlations at baseline were all highly significant (Spearmanʼs r-coefficients between 0.31 and 0.8, all p < 0.05). None of the correlations of parameter changes over time were significant (all p > 0.05).Conclusion Whereas a robust correlation was observed at baseline between the structural (OCT and OCTA) and functional (VF MD) parameters, none of the examination modality could predict a change in the other modalities during the 1-year period. Results confirm the necessity of regularly performing both the structural and functional examinations in our glaucoma patients.
Keywords: glaucoma; pathology; retina